Role of Macroeconomic Factors, Institutional Quality and Digitalization Towards Performance of Islamic Microfinance Institutions - Ahmed, Mushtaq; Isa, Mohamad Yazid (Johar Education Society, Pakistan (JESPK), 2023)
Islamic microfinance is widely accepted in Muslim-majority countries as Islamic microfinance products are based on Islamic principles. However, despite the extreme need and widespread popularity of Islamic microfinance institutions (IMFI), this sector is lagging behind conventional microfinance institutions with scarce literature to exhibits its performance at country-levels. The success of microfinance institutions is uneven in achieving both objectives, some achieve one objective, either financial or social, while some fail to achieve any objective altogether. In this line, study uses panel data of 35 Islamic microfinance institutions of OIC countries to investigate the impact of macroeconomic, macro institutional factors and digitalization on the financial and social performance of microfinance institutions in OIC countries from 2008 to 2019. The results from Pooled-OLS and System-GMM by using STATA found that macroeconomics and country-level institutional variables have complementary and rivalrous effects in IMFIs. In addition, digitization has a significant impact on the performance of (IMFIs). The study recommends to consider country-level environment and adoption of digitalization in policy making to enhance the simultaneous development of IMFIs